A better understanding of the structure of a wine market using the attribute of variety. (1st January 2012) - Cohen, Justin; Lockshin, Larry; Sharp, Byron
The enhanced value of exploring attributes in the description of the structure of a wine market has been shown. In this paper, the attribute of variety is highlighted to illustrate this fact. A sample of revealed preference data obtained from a loyalty programme of a high-end retail chain in Australia is evaluated using 'observed' performance measures, the 'double jeopardy' phenomenon, polarisation and duplication of purchase. The market is classified by variety into managerially useful segments of 'excess loyalty', 'niche' and 'change of pace' behaviour. The myth of a separate white and red wine category has been dispelled. This research confirms the emerging role of Australia in attribute-based wine market research in the 21st century.